'Effective' collisions in weakly magnetized collisionless plasma: importance of Pitaevski's effect for magnetic reconnection. (9th February 2016) - Zelenyi, Lev M.; Artemyev, Anton V.
Abstract : In this paper we revisit the paradigm of space science turbulent dissipation traditionally considered as myth (Coroniti, Space Sci. Rev., vol. 42, 1985, pp. 399–410). We demonstrate that due to approach introduced by Pitaevskii ( Sov. J. Expl Theor. Phys., vol. 44, 1963, pp. 969–979; (in Russian)) (the effect of a finite Larmor radius on a classical collision integral) dissipation induced by effective interaction with microturbulence produces a significant effect on plasma dynamics, especially in the vicinity of the reconnection region. We estimate the multiplication factor of collision frequency in the collision integral for short wavelength perturbations. For waves propagating transverse to the background magnetic field, this factor is approximately$({\itρ}_{e}k_{x})^{2}$ with${\itρ}_{e}$ an electron gyroradius and where$k_{x}$ is a transverse wavenumber. We consider recent spacecraft observations in the Earth's magnetotail reconnection region to the estimate possible impact of this multiplication factor. For small-scale reconnection regions this factor can significantly increase the effective collision frequency produced both by lower-hybrid drift turbulence and by kinetic Alfvén waves. We discuss the possibility that the Pitaevskii's effect may be responsible for the excitation of a resistive electron tearing mode in thin current sheets formed in the outflow region of the primary X-line.